High prevalence of genital Chlamydia trachomatis infection in women presenting in different clinical settings in Jamaica: implications for control strategies. Issue 6 (1st December 1999) - Dowe, G; Smikle, M; King, S D; Wynter, H; Frederick, J; Hylton-Kong, T
Abstract : OBJECTIVE: To determine the prevalence of genital Chlamydia trachomatis infection and risk factors in women attending family planning, gynaecology, and sexually transmitted disease (STD) clinics in Jamaica. METHODS: Endocervical specimens from 645 women including 238 family planning, 170 gynaecology, and 237 STD clinic attendees were examined for C trachomatis using a direct fluorescence assay (DFA) and culture. Investigations were carried out for the presence of other STD pathogens and demographic, behavioural, historical, and clinical data recorded for each participant. RESULTS: The prevalence of C trachomatis infection was 35%, 47%, and 55% in family planning, gynaecology, and STD clinic clients, respectively. The performance of the DFA was comparable to that of culture in screening for C trachomatis. Logistic regression analysis revealed that the independent risk factors for C trachomatis infection were non-barrier contraceptive methods in family planning clients (OR = 2.1; 95% confidence interval (CI) = 1.2-3.9; p = 0.0110), cervical ectopy in gynaecology clients (OR = 3.9; 95% CI = 1.4-10.6; p = 0.0076) and concomitant Trichomonas vaginalis infection in STD clients (OR = 3.5; 95% CI = 1.8-6.8; p = 0.003). Age, number of sex partners, and reason for visit were not identified as risk factors for C trachomatis infection. CONCLUSIONS: Consistently high prevalence of C trachomatis infection occurs in Jamaican women. Universal screening or presumptive treatment should be evaluated as prevention and control measures for C trachomatis infection in this population where all women appear to be at risk.